BASIC MORAL STANDARDS IN ETIC SYSTEM OF I. KANT - A. M. Sklyarovа (Дискурс)
The article reviews main items of I. Kant ethical system based on I. Kant work “Critique of Pure Reason”, “Groundwork of the Metaphysics of Morals”, “Prolegomena to Any Future Metaphysics”. The article analyzes the main issues of I. Kant philosophy: will autonomy as moral maxim; freewill; moral imperatives: hypothetical, categorical, ethics of duty, postulates and principles of morality; the idea of immortality of soul and the existence of God. The article focuses special attention on critique of Kant moral tenets: formalism, eudemonism, rigorism. The article marks actual aspects of Kant moral philosophy.